The attitude and knowledge of pediatricians and family physicians toward COVID-19 vaccination in children: A cross-sectional study - Mahmoud A. Alfaqih; Ebaa Y. Ababneh; Galya A. Almansi; Sara A. Marashdeh; Alaa A. Khazandar; Ahmad M. Said; Ayman G. Mustafa (Taylor & Francis Group, 2023)
COVID-19 vaccines to children are expected to reduce the transmission of the disease to high-risk groups and achieve herd immunity in younger populations. A positive attitude toward COVID-19 vaccination in children among healthcare workers (HCWs) is predicted to reduce parents' hesitancy to vaccinate their children. This study aimed to assess the knowledge and attitude of pediatricians and family physicians toward COVID-19 vaccination in children. A total of 112 pediatricians and 96 family physicians (specialists and residents) were interviewed to assess the level of knowledge, attitude, and perceived safety of COVID-19 vaccines for children. Physicians willing to receive regular COVID-19 vaccination (analogous to the influenza vaccine) had significantly higher knowledge and attitude scores (P < .05). Multivariate analysis indicated that a higher knowledge score and having at least five years of experience as a specialist were significantly associated with a positive attitude among pediatricians or family physicians (P < .05). Pfizer/BioNTech was the preferred COVID-19 vaccine in children among physicians of both groups (>67%). Around 71% of physicians believed COVID-19 vaccines for children do not cause or worsen any health condition. Educational and training programs that increase the knowledge of physicians about COVID-19 vaccines and their safety in children are recommended to inform a more positive attitude.